Pengembangan E-learning berbasis Edmodo pada mata pelajaran Ilmu Pengetahuan Alam untuk siswa kelas VIII SMP - Hidayati Rahmatika (Universitas Negeri Padang, 2022)
This study aims to develop edmodo-based e-learning learning as a support for natural science learning in SMP Negeri 16 Padang. This type of research is research and development (Research and Development / R & D). The product development model used in this study is the flow from Thiagarajan namely 4 - D (Four-D Models) .. The results of the validity of the aspects of the media and material shows that edmodo-based e-learning is valid with light revisions, and from the point of view of students The edmodo-based learning produced is very practical to use. The results of testing the effectiveness of the product, Edmodo has been effective for use in science learning for VIII SMP with an average posttest higher than pretest. Thus it can be concluded that edmodo-based e-learning products are suitable for use in the learning process.